The Lancet Commission on medicine, Nazism, and the Holocaust: historical evidence, implications for today, teaching for tomorrow - Czech, Herwig; Hildebrandt, Sabine; Reis, Shmuel P; Chelouche, Tessa; Fox, Matthew; González-López, Esteban; Lepicard, Etienne; Ley, Astrid; Offer, Miriam; Ohry, Avi; Rotzoll, Maike; Sachse, Carola; et al. (The Lancet (British edition), 2023)
What happened under the Nazi regime has far-ranging implications for the health professions today, and virtually every debate about health professional ethics can gain from an understanding of this shameful history—from questions regarding the beginning and the end of life, to health professionals' roles as economic actors or as agents of the state. [...]we offer here a new educational paradigm, which we term history-informed professional identity formation. Teaching should focus on learning core facts and reflecting on the implications of this history for present and future health-care practice, including the responsibility of medical professionals and their institutions to uphold human rights within clinical practice, research, and public policy, and to combat antisemitism, racism, and other forms of discrimination. The history of medicine, Nazism, and the Holocaust shows that values and ethics in health care are not immutable but change over time dependent on cultural, social, economic, and political factors (and particularly when placed under pressure). [...]values and ethics constantly need to be critically assessed and reinforced to protect them from potentially becoming exclusionary and inhumane.